Clostridium difficile infection in Johannesburg, South Africa. Issue 5 (20th October 2018) - Godinho, Lee-Anne; Feldman, Charles
ABSTRACT: Objectives : The incidence of Clostridium difficile infection is increasing, resulting in significant in-patient morbidity and mortality. We describe the characteristics of Clostridium difficile infection in patients admitted to a tertiary Academic Hospital in Johannesburg, South Africa. Methods : This was a retrospective record review of 154 adult in-patients with confirmed Clostridium difficile infection undertaken between 1 January 2013 and 30 June 2014. Results : Overall, 83 (53.9%) patients were female and the median age was 39 years. The most common symptoms were watery diarrhea (92.9%) and fever (27.3%). Overall, 145 (97.9%) patients had been exposed to antibiotics in the last 30 days, 54 (35.1%) to immunosuppressives, 48 (31.2%) to gastric acid suppressants, and 65 (42.2%) patients had previous hospital admissions. Only two cases were community-acquired. In total, 73 (47.4%) patients died. There was no difference in outcomes of HIV-positive patients compared to HIV-negative patients; however, the clinical features were more marked in the HIV-negative patients. Non-survivors tended to have a greater number of severity indicators compared to the survivors. Conclusion : Patients with Clostridium difficile infection in this study were younger and had a higher mortality than that reported in the Western world. Most infections were hospital-acquired.